Concentration of Peptides in Extracts of Cryopreserved Fragments of Pig and Piglet Organs and Role of Endogenous Proteases in Their Formation - Rohoza, Liliya A.; Bespalova, Iryna G.; Galchenko, Sergiy Ye.; Semenchenko, Oleksandr Yu.; Sandomirsky, Borys P. (Problems of Cryobiology and Cryomedicine, 2014)
Production of medicines based on bioactive peptides is one of the approaches of correcting body dysfunctions. We have developed the method to procure these peptides, which includes cryopreservation of organ fragments. The concentration of peptides in the extracts obtained from non-cryopreserved and cryopreserved fragments of pig and piglet organs was investigated, depending on the used cryoprotectant and incubation period. The role of endogenous proteases in formation of peptides during incubation of organ fragments was discovered. It was found that after 60-min incubation of heart fragments of pigs and piglets, cryopreserved with polyethylene oxide with MW of 1500 (PEO-1500), the peptide concentration in supernatant was significantly higher than after incubation of those of control and cryopreserved with either glycerol or PEO-400. Yield of peptides into supernatant from fragments of pig spleen and piglet skin, cryopreserved with PEO-400 or PEO-1500 was higher than that from non-cryopreserved or cryopreserved under protection of glycerol ones. Following incubation of both control and cryopreserved (cryoprotectant PEO-1500) fragments of organs with protease inhibitors, the peptide concentration in the supernatant was significantly lower than without their addition. It has been found that after introduction of protease inhibitors the amount of low molecular peptides in extracts decreased. Probl Cryobiol Cryomed 2014; 24(2):122-139.